PENGARUH PELATIHAN, DISIPLIN KERJA, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN BAGIAN MEKANIK DALIMO JAYA MOTOR PEKANBARU - Sudarman Aryani; Garnasih Lestari Raden; Marzolina Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study is to ascertain how mechanics at Dalimo Jaya MotorPekanbaru's performance is affected by training, work discipline, andcompetence. The population as a whole is used as a research sample in this study,which employs the census method or saturation sampling, with a total of 65participants. Primary data in this study were collected using a questionnaire asan instrument to prove the results of the study, to test the hypothesis in this studyused multiple linear regression analysis through the SPSS program. The resultsshowed that: 1) the training variable has a positive and significant impact on theemployee performance variable of mechanics Dalimo Jaya Motor Pekanbaru, 2)the work discipline variable has a positive and significant impact on the employeeperformance variable of mechanics Dalimo Jaya Motor Pekanbaru, 3) thecompetence variable has a positive and significant impact on the employeeperformance variable of mechanics Dalimo Jaya Motor Pekanbaru. 4) thetraining, work discipline and competence variables simultaneously have a positiveand significant impact on the employee performance variable of mechanicsDalimo Jaya Motor Pekanbaru. Keywords: Training, Work Discipline, Competency, and Performance.